Expand, grow, thrive : 5 proven steps to turn good brands into global brands through the LASSO Method - Canalichio, Pete (Emerald Publishing Limited, 2018)
Using powerful storytelling and unique access to the personal perspectives of top-flight marketers who have developed truly world-class business growth programs, Pete Canalichio shows us how successful marketers have extended and expanded their brands, and the challenges they have had to overcome along the way. The LASSO model (Lateral; Addictive; Storied; Scalable; Own-able) offers a simple, accessible and effective way for marketers to get their heads around the desired attributes of highly successful growth programs. With insightful advice, anecdotes and tips from leading brand licensing professionals, household names like Coca-Cola and Disney, senior marketers and inspiring individuals, Canalichio has created a measured and proven "Think Big, Get Big" framework to truly help your brand first expand, grow successfully, and ultimately thrive.
Includes bibliographical references and index.
Print version record
Keywords: Marketing; Business & Economics -- Marketing -- General; Sales & marketing